Rehabilitation of COVID 19 Patients, Bangladesh Perspective - Rahman, Md Shahidur (Journal of Bangladesh College of Physicians and Surgeons, 2022)
The global outbreak of COVID 19 has created an unprecedented challenge to the society. America, Europe and India were catastrophic sufferers from this virus next to China. They had highest number of daily morbidity and mortality in the global context. Bangladesh is facing terrible experiences of dealing with this pandemic and making a tremendous turmoil in health and economic sector. Our healthcare system is overburdened with critically ill patients. Disability arising out of neurological, pulmonary, neuromuscular, and cognitive complications, need to be addressed by rehabilitation professionals. Many patients presenting with COVID-19 will have no specific airway clearance needs.There have been no reports of COVID-19 positive patients having high secretion loads that would require intensive chest physiotherapy or postural drainage. In Bangladesh in ICU settings physiatrist or physiotherapists are not directly involve in respiratory care management. In mild to moderate cases advice about a post-acute care breathing exercises, other musculoskeletal exercises, bed positioning and pressure sore care are helpful. In Bangladesh medical care facilities are not adequate in corona care hospitals especially in peripheral medical college or hospital. Many patients are dying of shortage in oxygen supplies and lack of availability of ICU. Post discharged plans of comprehensive rehabilitation are grossly neglected in discharged certificate. Our national guidelines on corona management do not have any instructions on rehabilitation management at any point. The objectives of this fast review article on corona pandemic are to highlight the global scenario and our limitations in the rehabilitation management of COVID 19 patients particularly post discharged patients and patients with long COVID complications. J Bangladesh Coll Phys Surg 2022; 40: 52-56